Halal Development: Trends, Opportunities and Challenges Proceedings of the 1st International Conference on Halal Development (ICHaD 2020), Malang, Indonesia, October 8, 2020 - Pratikto, Heri; Taufiq, Ahmad; Voak, Adam; Deuraseh, Nurdeng; Nur, Hadi; Dahlan, Winai; Purnomo, Agus (Taylor & Francis, 2021)
The increasing demand for halal products, including goods and services, every year, especially for food and beverages, has resulted in a growing need for products with halal guarantees. Along with the increasing trend of the global demand, it has resulted in an increase in producers of halal food and beverages in both Muslim and non-Muslim countries. In addition the demand for halal tourism is also increasing. Indonesia is one of the largest Muslim countries in the world. However, there are still many Muslim consumer actors and Muslim producer actors who do not yet have an awareness of the importance of complying with the provisions of Islamic law in consuming and producing goods and services. There are still many restaurants and hotels that serve food and drinks that are not certified halal. There are still many food, medicinal and cosmetic products that are not halal certified. But now many secular countries such as France, Canada, Australia, the United States, Britain are also halal certified with the aim of meeting the Muslim demand for halal products for food and beverage, including for halal tourism. Starting from the development of the halal industry both in the fields of food, beverages and services, an International Seminar was held, which provides a more complete understanding of halal products, current halal developments and can serve as motivation to produce halal products, providing research results from the topic of halal development. The international seminar, entitled International Conference on Halal Development, listed speakers from several countries able to provide an overview of the halal development of several countries. This book contains a selection of papers from the conference.